Effects of electroacupuncture on endothelial function and circulating endothelial progenitor cells in patients with cerebral infarction. (August 2015) - Lee, Sanghoon; Kim, Weon; Park, Jimin; Jang, Hyun Hee; Lee, Seung Min; Woo, Jong Shin; Kim, Hyun Soo; Lee, Kyung Hye; Kwon, You‐Jung; Lee, Ungin; Kim, Jin Bae; Kim, Woo Shik; et al.
Summary This study evaluated the effects of electroacupuncture (EA) on endothelial function and endothelial progenitor cells (EPC) in patients with cerebral infarction. In a randomized, placebo‐controlled, crossover study, 20 patients with cerebral infarction were randomized into two treatment groups: EA or placebo. Before and after each intervention, pulse amplitude tonometry (PAT) was used to assess endothelial function and peripheral blood was analyzed for the number of EPCs. Circulating EPCs were quantified by flow cytometry as CD45lowCD34+KDR2+ cells. Plasma vascular endothelial growth factor (VEGF) and interleukin (IL)‐10 levels were measured. Seven days later, crossover was performed on each group, with each group receiving the other treatment using the same protocol. The PAT hyperemia ratio ranged from 1.57 ± 0.41 to 2.04 ± 0.51 after EA, representing a significant improvement (P = 0.002); however, there was no improvement in the placebo group (P = 0.48). Circulating EPCs, as measured by flow cytometry, increased to 110.6 ± 74.3/100 μL in the EA group (P = 0.001) but did not change in the placebo group (45.9 ± 35.3/100 μL, P = 0.08). The increases in the number of EPCs and the PAT ratio after treatment were correlated (r = 0.78, P < 0.001). Plasma VEGF levels increased with EA compared to baseline (261.2 ± 34.0 vs 334.9 ± 80.5 pg/mL, P = 0.003). The number of circulating EPCs was positively correlated with plasma levels of VEGF (r = 0.50, P = 0.02). In conclusion, EA induced improvement of EPC levels and the PAT ratio in patients with cerebral infarction.